Powtoon Animation Video Media Based on Contextual Teaching and Learning on Pancasila Material - Cahyani, Dita Maulida; Sunarso, Ali (Universitas Pendidikan Ganesha, 2024)
The lack of types of learning media in PPKn learning content in Pancasila material in class III impacts low PPKn learning outcomes. This research aims to develop a powtoon animation video based on contextual teaching and learning on Pancasila material for class III elementary school. This research uses Research and Development (R&D) research using the ADDIE method. The subjects of this research were 1 learning materials expert and 1 learning media expert. There were 33 product trial subjects in this research. The methods used to collect data were observation, interviews, questionnaires, documentation, and tests. The data collection instruments are in the form of questionnaires and test questions. The techniques used to analyze the data are qualitative and quantitative descriptive analysis and N-gain. The research results are the assessment of the media expert test 92.5%, the material expert test 86.25%, the small group test 90%, the significant group test 95%, and the class teacher test 90% so that you get a decent qualification. The results of N-gain stated that Powtoon animation video media based on Contextual Teaching and Learning has a category suitable in learning Pancasila material for PPKn content. It was concluded that Powtoon animated video media is good to use, effective, and ideal for learning. The implication of this research is that the Powtoon animation video developed can be used in Civics learning.